2012
DOI: 10.2298/avb1201053j
|View full text |Cite
|
Sign up to set email alerts
|

Plasma malondialdehyde, biochemical and haematological parameters in standardbred horses during a selected field exercise test

Abstract: The aim of the present study was to determine changes in plasma malondialdehyde (MDA) concentration and haematological and biochemical profiles in 10 clinically healthy standardbred horses subjected to a selected field exercise test. Correlations between plasma MDA, the main lipid peroxidation end-product, and muscle enzymes: creatine kinase (CK) and aspartate aminotransferase (AST) were determined in serum samples. Venous blood samples for determination of selected blood parameters were collected, immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…It is the most commonly used marker of the level of lipid peroxidation in exercise and sport studies [110]. Several studies have confirmed the increased lipid peroxidation during different forms of physical activity in sport horses [19,21,23,24,27,31,32,34,111]. Similarly, in the present study, plasma MDA concentration increased significantly after physical activity in both the placebo and CoQ 10 supplemented groups, while no significant increase was observed in the vitamin E and CoQ 10 + Vit.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It is the most commonly used marker of the level of lipid peroxidation in exercise and sport studies [110]. Several studies have confirmed the increased lipid peroxidation during different forms of physical activity in sport horses [19,21,23,24,27,31,32,34,111]. Similarly, in the present study, plasma MDA concentration increased significantly after physical activity in both the placebo and CoQ 10 supplemented groups, while no significant increase was observed in the vitamin E and CoQ 10 + Vit.…”
Section: Discussionsupporting
confidence: 80%
“…Physical activities of different intensities have been shown to induce oxidative stress not only in human athletes but also in horses; namely endurance horses [19][20][21][22][23], show jumpers and dressage horses [24,25], pentathlon horses [26], Marremmana racehorses [27], Thoroughbred racehorses [28][29][30], Standardbred trotters [31,32], and horses subjected to various moderate and intense treadmill exercise tests [33][34][35][36]. Lipid peroxidation is the most common consequence of exercise-induced oxidative stress and can lead to the release of muscle enzymes into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise greatly increased the CK values in both groups of horses [ 42 ]. This is related to the change in permeability of the cell membrane of musculoskeletal cells due to oxidative peroxidation [ 43 , 44 ]. Therefore, this enzyme is a marker of muscle damage that increases in value after intense/prolonged efforts [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sporer et al highlighted the use of metabolites as potential biomarkers of stress following transportation in beef bulls [21]. Physical exercise, especially when it is intense, not only induces oxidative stress but can also modify the animal's physiological metabolism, leading to changes in physiological, hematological, and biochemical variables [8,[35][36][37][38]. The metabolic profiles described for Lidia cattle are similar to those described for other domestic cattle breeds [42], although some serum biochemical variables of this breed differ significantly from other cattle breeds, due to the particular temperament characteristics of this breed [17,20,42].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise not only induces oxidative stress, but can also modify the physiological animal metabolism, leading to changes in hematological and biochemical variables [8,[35][36][37][38][39][40]. Knowledge of metabolic values is essential to monitor the normal homeostatic functioning of the organism.…”
Section: Introductionmentioning
confidence: 99%